Comunicação e constituição do sujeito nas redes de criação: estudo das cartas de Ana Cristina Cesar, Clarice Lispector e Frida Kahlo - Souza, Gilda Sabas de (2013)
This thesis questions the communicative aspects and the constitution of the subject through the creation process of Ana Cristina Cesar, Clarice Lispector and Frida Kahlo. Our corpus consists of books with letters by Ana Cristina Cesar, Clarice Lispector and Frida Kahlo and five Frida Kahlo s self-portraits. Our theoretical framework is grounded on the works of Flusser in the field of communication. The definition and structure of letters is based on the thoughts of Anonymous from Bologna, Caio Junior Victor, Michel Foucault and Mark Moraes. The analysis of self-portraits relies on reflections of Katia Canton, J. Moulin and Ernst Rebel; on the process of creation as a network, semioticallybased (Peircean line) we resorted to Cecilia Salles s research. The methodology covered the identification of the elements of creation that were significantly repeated, thus lending themselves to some generalizations about their creative processes. From this perspective the thesis discusses the concept of letter and the structure of the letters analyzed as well as contemplates this communicative medium along the studies of the processes of creation as a network, focusing on the marks left by authors in the constitution of the subjects of creation. Finally, we propose a possible analogy between the authors way of writing letters and the process of creating Frida Kahlo s self-portraits. The results are: discussion of the concept of letter, analysis of the structure of letters, reflection both on the communicative act in the creation process and on the constitution of creator subjects and finally on the analogical relationship between the writing of letters and the process of creating self-portraits